Calculation Methods of Topographic Factors Modification Using Data Digital Elevation Model (DEM) To Predict Erosion - Hengki Simanjuntak; Hendrayanto .; Nining Puspaningsih (Department of Forest Resources Conservation and Ecotourism - IPB University, 2017)
Erosion is a crucial information for sustainable management of land resources within a particular watershed. The information of erosion is needed for land resource management planning, and is generally counted by USLE (Universal Soil Loss Equation). One of the parameters in USLE is topographic factor (LS). The determinations of LS in erosion estimation model are vary, both in terms of LS factor equation, as well as in terms of the length of the slope (λ) and slope (s) measurements. There are at least 3 methods used to calculate slope factors in spatial operation, i.e (1) Input of the LS Value from Table (INT), (2) Flow accumulation, and (3) Cell Size. The study was designed to obtain a method of calculation that gives the smallest topographic factor and in order to obtain a LS factors that similar to the slope information. Research location in Kampa Sub watershed, The LS determination in Kampa Sub watershed basically are with (INT) and without calculating λ and s. INT method is determination without calculating λ and s, LS value is generate from the contour map and DEM SRTM by giving LS value from table reference of LS value. The Flow Accumulation and Cell Size are determination of LS Value by calculating λ and s. The Flow Accumulation method modifies the determination of λ and s using the middle value of s, λ per land use, and λ and s per cell. Cell Size method determines λ using the amount of cell size. The results showed that the “cell size” and